PENGARUH BIAYA PENDIDIKAN TERHADAP MUTU SEKOLAH DI SEKOLAH MENENGAH PERTAMA SWASTA - Dea Chairyani; K.A Rahman; Muazza Muazza (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2022)
Abstract: This study aims to determine the effect of education costs on school quality in private Junior High Schools. This research was conducted in one of the Junior High Schools in Jambi City. The method used is a qualitative approach with data collection techniques, namely observation and interviews. Based on the results of observations and interviews that have been carried out, it was found that there was a direct positive influence between the cost of education on the school quality. High school fees are very influential in carrying out activities carried out in schools to improve the quality of the school. The implication of this research is that efforts to improve the quality of schools can be done through education costs.Keywords: Cost and School Quality.